Robust fault-tolerant control for power systems against mixed actuator failures. (November 2016) - Kaviarasan, B.; Sakthivel, R.; Kwon, O.M.
Abstract: This paper employs linear matrix inequality (LMI) based optimization algorithm to develop a method for designing fault-tolerant state feedback controller with mixed actuator failures for power systems subject to random changes. Meanwhile, the random abrupt changes are determined by a finite set Markov chain so the considered system is equivalently represented as a discrete-time Markov jump linear system (MJLS). Further, due to the variations of loading conditions in power system, an uncertainty term is incorporated to MJLS. For the proposed system, we construct a novel actuator fault model containing both linear and nonlinear terms which is more general than the conventional actuator fault models. The main purpose of this paper is to design the robust fault-tolerant controller such that for all possible actuator failures, time-varying delays and admissible parameter uncertainties, the closed-loop uncertain discrete-time MJLS is robustly stochastically stable. Based on free-weighting matrix approach and linear matrix inequality theory, a new set of sufficient conditions that guaranteeing the robust stochastic stability is presented by choosing an appropriate Lyapunov–Krasovskii functional candidate. In addition, a single-machine infinite-bus (SMIB) power system is considered as an application example and its simulation results demonstrate the effectiveness of the proposed design techniques.